Development and Evaluation of Rhinoplasty Spreader Graft Suture Simulator for Novice Surgeons - Oh, Connie J. (Laryngoscope, 2018)
OBJECTIVE: Surgical simulators aimed at mimicking elements of rhinoplasty surgery, specifically those aimed at improving cartilage suturing, are not available. Here we present a surgical simulator for spreader graft placement that uses cartilage rather than synthetic materials, and gauge improvement using objective measures for suture placement accuracy, speed, and efficiency of hand motion. METHODS: 22 otolaryngologists in two groups (residents (10) and experts (12)) were instructed to secure the two spreader graft specimen into position with three mattress sutures on a nose model that used porcine septal cartilage as a proxy for the human counterpart. Hand motion was tracked using an electromagnetic position sensing device. Time required to complete the suture task, total hand displacement, cumulative number of hand motion direction changes, and accuracy of suture insertion were measured. These measurements were compared between the two cohort groups for construct validity. The subjects completed a survey to evaluate realism and value of the model. RESULTS: The expert group had a lower mean time required to complete the task (p < 0.05), total hand displacement (p < 0.01), and number of hand motion direction changes (p < 0.001). No significant difference was observed between the two groups in suture precision measurement. The subjects agreed on the face validity and usefulness of the trainer. CONCLUSIONS: Our study suggests that the simulator may be a useful tool to objectively gauge suturing efficiency. Devices such as this may be useful for developing skill with suturing cartilage tissue and potentially be used as a means to assess resident acquisition of surgical skill.